IMPLEMENTASI SUPERIOR CUSTOMER VALUE DALAM PERSAINGAN OBYEK WISATA - Rusdan Rusdan; Sulhaini; Rahman Dayani (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2020)
The purpose of this study is to fill the research gap with the hope of contributing to the development of consumer behavior models that are part of Consumer Behavior lectures in the field of Marketing Management studies.The research method used is descriptive method with a sample survey approach in some populations. This Study population was tourists who had visited one of the natural attractions (Botanic Garden and Pancingan Market). There are 50 people in each location determined accidentally. The analytical approach used is model of the Consumer Matrix. The conclusions that can be drawn are; (a) Pancingan Market is in the East with low price perception (cheap) and high PUV (perceived use value), (b) Botanic Garden is in the West path with higher price perception (expensive) and PUV perception or perceived use value low, (c) Position of the Pancingan Market seen from the perception of price and perceived value of use to have a better position compared to the Botanic Garden, (d) All service elements in the Pancingan Market and Botanic Garden still do not provide good performance and need attention serious developing.